Emotional Intelligence, Trust, and Functional Behavior: Longitudinal Study of Achievement Approach to Leadership Emergence - Kim, Kihwan; Kim, Joseph; Antonio, Justin; Laws, Janell (Journal of Organizational Psychology, 2021)
Leadership emergence refers to the phenomenon where an individual voluntarily takes a leadership role even when there is no designated leader. There have been many studies that investigated the antecedents of leadership emergence but few studies have investigated the integrative process of leadership emergence. Based on the achievement approach to leadership emergence, the current study attempts to explore how an individual’s trait, state, and behavior are related to leadership emergence. The study found that an individual with high emotional intelligence is more likely to emerge as a leader by perceiving trust and showing task behaviors. We collected longitudinal data from 171 participants (43 groups) who played a business simulation game as a group task for 11 weeks. The data analysis revealed that emotional intelligence is positively related to trust, which in turn has a positive impact on task behavior. Additionally, task behavior has a positive impact on leadership emergence. In the study we discussed implications, limitations, and future research issues.